Export Policy Role in Reviving German Economy (Latakia University Journal - Economic and Legal Sciences Series, 2021)
After the global financial crisis and the subsequent sovereign debt crisis that hit European economies in 2010, the German economy was able to recover faster than the others, achieving what has been called the "second German miracle". While some researchers had attributed this miracle to the monetary policy of the European Central Bank which is largely biased towards Germany (as the strongest economy in the region), others attributed it to the German economy’s reliance on the export sector and its successful strategy before and during the 2010 crisis. Accordingly, This study aimed to determine the extent of the contribution of the German export policy to achieve that miracle in order to extract some lessons. To this end, the impact of the export growth rate on the German economy has been analyzed since the outbreak of the European sovereign debt crisis in 2010 until the end of 2019; This is done by analyzing the changes in both the export growth rate and the main indicators of the German economy (growth, inflation, and unemployment rates) graphically and statistically depending on ARDL methodology  in order to test the existence of a relationship in the long and short term.The research concluded that there was a significant effect of the export growth rate on growth and unemployment rates, while it didn’t have any effect on the inflation rates. That is, the German export-dependent growth model has relatively contributed to the recovery of the economy and the improvement of its indicators, depending on its export strategy on the one hand, the strength and resilience of the economy on the other hand, and on German’s benefit from the European crisis on the third hand.